Using SQ4R to Improve Students’ Reading Comprehension in Vocational High School - Mahastu, Puput Jianggi; Fahas, Rida; Husaini, Rizqi; Richy, Dedy (Universitas PGRI Semarang, 2022)
This study intends to enhance the first semester comprehension skills of Class X TKJ students at SMK Nagara Kedunggalar using the SQ4R approach. Action research in the classroom is used in the study. Only one cycle of three sessions was used for the research. Participants in the study include the author, an English teacher, and 26 TKJ students in the tenth grade from SMK Nagara Kedunggalar. Both qualitative and quantitative data are present in this study. The qualitative information was gathered through student and English teacher interviews, as well as observation of the teaching and learning process. The results of the pre- and post-tests for reading comprehension are used to generate the quantitative statistics. The three action research methodologies are used to conduct the study in a methodical manner. They include preparation, execution, observation, and reflection. The pupils must meet five benchmarks, including the ability to identify the main concept of a narrative work, identify references and vocabulary, and create a conclusion or summary. Additionally, the students' interest and participation can be increased by using the SQ4R approach. The majority of students are able to get past whatever issues they may have with the signs. According to the advancement of the mean value of the students' pre-test and post-test scores, the implementation of the SQ4R approach can improve the students' reading ability. Their post-test scores had a mean value of 83 while their pre-test scores had a mean value of 39. This accomplishment demonstrates how the SQ4R approach can help pupils' reading comprehension skills.